PERILAKU MENYONTEK PADA SISWA DITINJAU DARI KEPERCAYAAN DIRI DAN STRATEGI COPING - Solagrasia, Kartika (TALENTA, 2014)
Cheating behavior is one of education phenomena that often appearing in the teaching learning process. But the teachers and educator are still continues to confuse because they have not managed to find a method to stop habit cheated of the students. One of the factor which influence cheating behavior is the pressure to got good grades in examinations and will be the best achievement. ThisÂ  studyÂ  aimsÂ  toÂ  determineÂ  theÂ  correlationÂ  betweenÂ  selfÂ  confidenceÂ  with cheatingÂ  behaviorÂ  andÂ  correlationÂ  betweenÂ  copingÂ  strategyÂ  withÂ  cheatingÂ  behaviorÂ  in examinations.Â  MeasuringÂ  instrumentsÂ  wereÂ  usedÂ  areÂ  CheatingÂ  BehaviorÂ  Scale,Â  Self Confidence Scale and Coping Strategy Scale. The population of the research is Surakarta I Christian senior high school students while the number of sample is 60 people, which is obtained through byÂ  cluster random sampling technique. The data analyze technique in thisÂ  researchÂ  useÂ  theÂ  doubleÂ  linierÂ  regressionÂ  analysisÂ  withÂ  SPSS forÂ  WindowsÂ  Release 16,0. The resultsÂ  ofÂ  data analysisÂ  showed thatÂ  thereÂ  wasÂ  notÂ  significant correlation betweenÂ  selfÂ  confidenceÂ  withÂ  cheatingÂ  behaviorÂ  inÂ  examinationsÂ  getÂ  obtainedÂ  ÏÂ  value equalÂ  toÂ  0,459Â  >Â  0,05.Â  SubsequentÂ  dataÂ  analysisÂ  showedÂ  thatÂ  thereÂ  wasÂ  aÂ  significant correlation between coping strategy with cheating behavior in examinations, proofed to be obtain Ï value equal to 0,000 < 0,05. The result means variable coping strategy covers internal aspect can be become predictor to predict or measure cheating behavior. Keyword : cheating behavior, coping strategy, self confidence